Importance of Pathya Apathya in Shalakya Practice – A Conceptual Study - Pramila; Fayaz, Shamsa (International Research Journal of Ayurveda & Yoga, 2024)
Introduction: Ayurveda emphasizes on both prevention and curative aspects, which are of utmost importance in the restoration of health. Through the principles of Pathya Apathya, our Acharyas have equipped us with the necessary knowledge to prevent and manage lifestyle disorders related to ear, nose, and throat disorders. Regular observations assess the effectiveness of specific dietary habits and medications in the prevention of disorders. Knowledge of pathya and apathya Aahara and vihara tackle the disease at the grassroot level. Materials and Methods: Information on Pathya Apathya in Shalakya Tantra was gathered from the Laghutrayi, the Brihattrayi and its commentaries, and other Ayurvedic texts. Results: Various Ahara Vargas, which describes the qualities of various food items, has been referenced in ancient scriptures. This conceptual study is an attempt to throw light on the importance of Pathya Apathya in disease as well as normal life. Conclusion: The concepts of Pathya and Apathya are important in the treatment of every disease as well as for prevention or for maintaining a healthy life. Ayurveda is an ancient medical practice that seeks to avoid human suffering from all forms of physical, mental, intellectual, and spiritual illnesses in addition to curing ailments. Numerous human illnesses have been related to an unhealthy lifestyle, and there has been a lot of emphasis on lifestyle disorders such as kidney diseases, diabetes mellitus, and cardiovascular disorders as well as ways to prevent them. Improper lifestyle has an impact on vision as well. Tobacco, alcohol, cigarettes, junk food, high-fat diets, prolonged exposure to strong light, prolonged computer use, and chronic stress are a few examples of behaviors that can harm the eyes.[1] Nowadays, due to a busy lifestyle, people have no time to follow a healthy lifestyle and are not able to follow the proper care for the body as well as of the sense organs. Slight impairment in diet and lifestyle patterns may result in unhealthy situations for a person and thus manifesting in various diseases. Ayurvedic scriptures suggest that specific lifestyle practices, such as adhering to dinacharya, ritucharya, sadvritta, and Pathya